Modeling of pressure build‐up and estimation of maximum injection rate for geological CO2 storage at the South Scania site, Sweden. Issue 3 (3rd September 2014) - Yang, Zhibing; Niemi, Auli; Tian, Liang; Joodaki, Saba; Erlström, Mikael
Abstract: Carbon dioxide (CO2 ) injection in deep saline formations causes pressure increase which may be detrimental to the mechanical integrity of the storage reservoir. Injection induced pressure build‐up is a limiting factor for CO2 injection rates and storage capacity. In this study, we extend a semi‐analytical solution (based on one‐dimensional, two‐phase, two‐component radial flow) for application to estimate pressure build‐up and maximum injection rate of CO2 at a field site (South Scania, Sweden) using the method of superposition of image well solutions to account for the straight‐line boundaries imposed by three fault zones. The semi‐analytical approach for estimating pressure build‐up is validated by comparison to numerical simulations based on TOUGH2‐ECO2N. We analyze injection pressure sensitivity due to uncertainty in reservoir parameters as well as boundary conditions. Maximum injection rates and pressure limited capacity estimates are presented. This work demonstrates the use of semi‐analytical solutions to analyze pressure limitation on storage capacity for realistic reservoirs with irregular (non‐circular) boundaries. It is also shown that the semi‐analytical approach can also be used to evaluate the benefit of having multiple injection wells in terms of increasing the injection‐pressure‐limited storage capacity. The methodology presented in this study is useful for screening analysis of storage sites as well as for operation design and optimization where pressure build‐up as a limiting factor influences the objective function.